منهج المرادي في الاستشهاد بالحديث النبوي من خلال كتابه: (الجنى الدّاني) - بن عطاء الله, يوسف; دباز, عبد الفتاح (جامعة الوادي - University of Eloued, 2023)
ملخص: يهدف هذا البحث إلي تناول منهج المرادي في الاستشهاد بالحديث النبوي، من خلال كتابه (الجنى الداني في حروف المعاني)، والملاحظ فيه قلة الاستشهاد بالحديث مقارنة بالقرآن الكريم والشعر العربي، مع ملاحظة عدم اشتراطه صحة الحديث فضلا على أن يكون متواتر اللفظ كما اشترط المانعون للاستشهاد بالحديث النبوي في القضايا اللغوية، ومنه تبين أن المرادي على نهج ابن مالك في الاستشهاد بالحديث النبوي، وغالبا ما يأتي به المرادي في اثبات الحكم أو نفيها وفق نوع النص شعرا ونثرا، ويَعُد الحديث مع القرآن من النثر في اطراد الحكم. Abstract: The current research aims at investigating the Muradi approach in inferring the prophetic hadith throughout his book: Eldjena Eldani. It was noted that it lacks inferring the hadith comparing to the Holy Qoran and the Arabic poesy. As it was observed that it does not care about the correctness of the Hadith, but its main focus is on pronunciation frequency as the rejecters oblige the inference of the prophetic hadith in linguistic issues. Thus, it is obvious that the Muradi follows Ibn Malek approach in inferring the prophetic hadith. The Muradi usually proves or denies judgments depending on the text, which can be poetey or prose. The hadith and the Holy Qoran are considered prose when sustaining the judgments
The Muradi Approach In Inferring The Prophetic Hadith Throughout His Book: Eldjena Eldani
مقال
Keywords: منهج المرادي؛ استشهاد؛ الحديث النبوي؛ الجنى الدّاني; Elmuradi approach; inference; the prophetic hadith; Eldjena Eldani.